2022
DOI: 10.1007/s10433-022-00707-0
|View full text |Cite
|
Sign up to set email alerts
|

Living longer, working longer: analysing time trends in working life expectancy in Germany from a health perspective between 2002 and 2018

Abstract: Population ageing poses growing challenges to social security systems, in particular to public pension funds. The study analyses how Working Life Expectancy (WLE) and Healthy Working Life Expectancy (HWLE) in terms of three health indicators developed in Germany. Based on the German Socio-Economic Panel (GSOEP) from 2002 to 2018 (n = 211,141), time trends in labour force rates, mental and physical Health-Related Quality of Life (HRQoL), self-rated health (SRH) and the respective combinations (health indicator*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 50 publications
3
12
2
3
Order By: Relevance
“…Nevertheless, comparisons with previous research can provide some insight into whether general trends and educational inequalities in the insurance population differ from the findings reported for the total German population obtained from survey data. Comparing our results with the WLE at age 50 based on the ILO labor force concept, the overall level of WLE tends to be lower than the survey-based results ( Heller et al, 2022 ; Loichinger & Weber, 2016 ). Similarly, the level of WLE at young working-age is lower in our study than those reported by Eurostat ( Eurostat, 2022a ) and another study based on the German Socio-economic Panel ( Heller et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…Nevertheless, comparisons with previous research can provide some insight into whether general trends and educational inequalities in the insurance population differ from the findings reported for the total German population obtained from survey data. Comparing our results with the WLE at age 50 based on the ILO labor force concept, the overall level of WLE tends to be lower than the survey-based results ( Heller et al, 2022 ; Loichinger & Weber, 2016 ). Similarly, the level of WLE at young working-age is lower in our study than those reported by Eurostat ( Eurostat, 2022a ) and another study based on the German Socio-economic Panel ( Heller et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 76%
“…Comparing our results with the WLE at age 50 based on the ILO labor force concept, the overall level of WLE tends to be lower than the survey-based results ( Heller et al, 2022 ; Loichinger & Weber, 2016 ). Similarly, the level of WLE at young working-age is lower in our study than those reported by Eurostat ( Eurostat, 2022a ) and another study based on the German Socio-economic Panel ( Heller et al, 2022 ). This is in accordance with our expectation and may be explained by the differences in the statistical methods used (Sullivan versus multistate life approaches) and because individuals with low SES (and therefore with low WLE) are overrepresented compared to the general German population.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations